PENGGUNAAN STRATEGI ‘MENULIS DISINI DAN SAAT INI’ SEBAGAI SALAH SATU STRATEGI UNTUK MENINGKATKAN KEMAMPUAN SISWA KELAS X DI SMAN 4 PEKANBARU DALAM MENULIS TEKS RECOUNT - Delfi, Syofia Delfi Syofia; ', Misnawati Misnawati; ', Syafri K Syafri K (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research is aimed to improve the ability of tenth grade students at SMAN 4 Pekanbaru in writing recount text by using ‘Writing in the Here and Now’ strategy and to find out what factors cause the improvements. This research is based on the problem faced by the students in which they tend to be passive in the classroom while learning writing. The research participant was36 students in X9 class at SMAN 4 Pekanbaru in academic year 2014-2015 chosen by random sampling technique. This research was divided into two cycles; first cycle consisted of three treatments and second cycle consisted of two treatments. In collecting data, there were two kinds of data that were used; quantitative data: using a pre-test and two post-tests, and qualitative data: using observation sheet and field notes. The research findings indicated that using ‘Writing in the Here and Now’ strategy as one of strategies to help students’ writing competences can improve the ability of tenth grade (X9) students at SMAN 4 Pekanbaru in writing recount text. It is proven by the improvement of students’ score from 67.5 in Pre-Test, 74.7 in Post-Test 1, to 80.2 in Post Test 2. Many factors that caused the improvements of students’ scores and habit in the teaching and learning process but the most important one is it is from themselves who have already understood and enjoyed writing recount text which brought their average score into 80.2.If the teacher would like to use this strategy, it is better to give interesting topics for the students to write and somehow this strategy needs a good atmosphere to make the students comfort and enjoy while writing their experience.Keywords: ‘Writing in the Here and Now’ Strategy, Writing Ability, Recount Text.